RANCANG BANGUN APLIKASI KOREKSI LEMBAR JAWABAN KOMPUTER MENGGUNAKAN METODE DETEKSI TEPI CANNY - Putra , Bayu; Kadek Dwi Nuryana , I; Augusta Jannatul Firdaus , Reza (Inovate, 2019)
Last Semester Evaluation is part of study result evaluation which use Computer Answer Sheet asthe place for student to write the answers. Computer Answer Sheet generally corrected by spesificscanner with the expensive price, so some school choose to correct the answer sheet manuallylike at Ar-Rahman Sumoyono Islamic Senior High School. To solve that problem, this researchis one of some solution which use the benefit of smartphone and digital image processingtechnology specially canny edge detection method. This prototype will combinate canny edgedetection method to find the edge of image and hough circle transformation to detect markedanswers. This prototype use the convertible canny parameter value by user, consider thebrightness value of every captured image is different. Result of detected answer with hough circletransformation will be tracked to determine the choosen answer. The choosen an swer by studentswill be saved in array, and will be matched with the answer keys which saved in SQLite database.The result of comparation between the result of detected answer with the real answer based on30 answer sheet samples is 91,41 %.Keywords: android, answer sheet, canny. .